2023
DOI: 10.3390/biom14010043
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated In Silico and In Vitro Approach for the Identification of Natural Products Active against SARS-CoV-2

Rosamaria Pennisi,
Davide Gentile,
Antonio Rescifina
et al.

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has provoked a global health crisis due to the absence of a specific therapeutic agent. 3CLpro (also known as the main protease or Mpro) and PLpro are chymotrypsin-like proteases encoded by the SARS-CoV-2 genome, and play essential roles during the virus lifecycle. Therefore, they are recognized as a prospective therapeutic target in drug discovery against SARS-CoV-2 infection. Thus, this work aims to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…As expected, GC376, used as a control, fully inhibited 3CL pro in the low nanomolar range and was moderately active against PL pro . Moreover, our studies revealed the inhibition of the viral protease PL pro by Camostat, a compound previously accepted as a specific inhibitor of the cellular protease TMPRSS2 [ 36 , 37 ]. Consequently, our findings propose a dual mechanism of action for Camostat, involving the inhibition of both viral PL pro and host TMPRSS2.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, GC376, used as a control, fully inhibited 3CL pro in the low nanomolar range and was moderately active against PL pro . Moreover, our studies revealed the inhibition of the viral protease PL pro by Camostat, a compound previously accepted as a specific inhibitor of the cellular protease TMPRSS2 [ 36 , 37 ]. Consequently, our findings propose a dual mechanism of action for Camostat, involving the inhibition of both viral PL pro and host TMPRSS2.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudovirusbased assays have facilitated the screening of natural compounds for their ability to inhibit SARS-CoV-2 entry into host cells. Furthermore, pseudovirus technology has been crucial in studying the mechanisms of action of potential antiviral compounds against SARS-CoV-2 and its variants [60][61][62][63][64][65][66][67][68][69][72][73][74][75][76][77][78][79][80][82][83][84][85]. Luteolin-7-O-glucuronide (L7OG) and folic acid (FA) showed promising entry inhibitory activity against SARS-CoV-2 pseudotypes harboring alpha and omicron spike proteins [60].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pseudovirus technology has been crucial in studying the mechanisms of action of potential antiviral compounds against SARS-CoV-2 and its variants [60][61][62][63][64][65][66][67][68][69][72][73][74][75][76][77][78][79][80][82][83][84][85]. Luteolin-7-O-glucuronide (L7OG) and folic acid (FA) showed promising entry inhibitory activity against SARS-CoV-2 pseudotypes harboring alpha and omicron spike proteins [60]. Similarly, dihydrotanshinone, E-64-C, and E-64-D were identified as effective against MERS-CoV by targeting the spike protein [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation